Preliminary Phytochemical Analysis, Anthelmintic, Insecticidal and Protective Effect of Dicliptera bupleuroides Nees in Ethanol-induced Gastric Mucosal Damage Rats: Phytochemical and biological activities of Dicliptera bupleuroides Nees - Akbar, Shehla; Ishtiaq, Saiqa; Ajaib, Muhammad; Hanif, Uzma (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Dicliptera bupleuroides Nees.is traditionally used as a general tonic, as a diuretic, in skin diseases, in snake bite, in fever, and in stomach troubles but limited literature found with the scientific ground. The objective of the present research is to prove the medicinal use of Dicliptera bupleuroides in anthelmintic, insecticidal, and antiulcer activity. Reference drug was albendazole (20 mg/ml) in anthelmintic, permethrin (239.5 μg/cm2 ) in insecticidal, ranitidine (50 mg/kg), omeprazole (20 mg/kg) and sucralfate (100 mg/kg) were used in antiulcer activity respectively. Time of paralysis and death was calculated in anthelmintic activity while the rate of % age mortality was calculated in insecticidal activity. Parameters such as mean ulcer indices and percentage ulcer inhibition, gastric volume, pH, mucous and protein contents were assessed in the ethanol-induced ulcer model. In the anthelmintic study ethyl acetate and n- butanol fraction showed the more significant results in comparison to reference drug (53/54 min paralysis and 92/108 min death time). No extracts showed insecticidal activity. N-hexane extract showed significantly (p < 0.05) reduced gastric lesion by 54.9% in rats at 50 mg/kg when compared to ranitidine at 54.2%, omeprazole at 69.5%, and sucralfate 53.6% respectively. Gastric volume, as well as total acidity, decreased when compared with positive control 3.9 ± 0.15, 98.1 ± 3.8 and chloroform fraction was 1.8 ± 0.2, 11.3 ± 4.6. Gastric volume, pH, and total acidity of chloroform extract were 1.8 ± 0.2, 6.8 ± 0.9, and 11.3 ± 4.6. Mucous and protein content of chloroform extract versus standard was 505.1 ± 16.9, 37.8 ± 4.4 439.0 ± 11.9, 454.3 ± 14.1, and 432.6 ± 14.8 respectively. The above findings concluded that Dicliptera bupleuroides have medicinal importance in various pharmacological aspects.